2021
DOI: 10.1021/acsami.1c00896
|View full text |Cite
|
Sign up to set email alerts
|

Diluted-CdS Quantum Dot-Assisted SnO2 Electron Transport Layer with Excellent Conductivity and Suitable Band Alignment for High-Performance Planar Perovskite Solar Cells

Abstract: An electron transport layer (ETL) with excellent conductivity and suitable band alignment plays a key role in accelerating charge extraction and transfer for achieving highly efficient planar perovskite solar cells (PSCs). Herein, a novel diluted-cadmium sulfide quantum dot (CdS QD)-assisted SnO2 ETL has been developed with a low-temperature fabrication process. The slight addition of CdS QDs first enhances the crystallinity and flatness of SnO2 ETLs so that it provides a promising workstation to obtain high-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…and vacuum permittivity, respectively. [ 38–39 ] The V TFL and N t of the 4‐AMTHP‐Ac‐modified CsPbIBr 2 PSC is 1.194 V and 3.10 × 10 16 cm −3 , respectively, lower than those of the pristine one (1.402 V and 3.64 × 10 16 cm −3 , respectively), indicating that the trap state of the 4‐AMTHP‐Ac modified CsPbIBr 2 film is significantly reduced.…”
Section: Resultsmentioning
confidence: 99%
“…and vacuum permittivity, respectively. [ 38–39 ] The V TFL and N t of the 4‐AMTHP‐Ac‐modified CsPbIBr 2 PSC is 1.194 V and 3.10 × 10 16 cm −3 , respectively, lower than those of the pristine one (1.402 V and 3.64 × 10 16 cm −3 , respectively), indicating that the trap state of the 4‐AMTHP‐Ac modified CsPbIBr 2 film is significantly reduced.…”
Section: Resultsmentioning
confidence: 99%
“…In the monolayer of SnO 2 , additive is employed to achieve this aim. Same as the TiO 2 , the additive using in SnO 2 includes metal ion (e.g., Li + , 422 Mg 2+ , 423,424 Eu 3+ , 397 Y 3+ , 425 Zr 4+ , 426 Nb 5+ 427,428 ), function material (e.g., TiCl 4 , 429 KCl, 430 RbF, 393 Eu‐WO x , 431 MXene, 394,432,433 NH 4 F, 403 CdS, 434 phosphoric acid, 435 , 435 g‐C 3 N 4 , 436 EDTA, 437 ionic liquid, 406 SPF, 438 PEG, 439 graphene, 440 carbon, 441,442 fullerene and its derivatives, 443–446 ) and plasma gas (e.g., N 2 , 447 Ar and O 2 448 ). For example, Park et al 422 demonstrated that Li + can enhance the conductivity and induce a downward shift of HOMO and LUMO of SnO 2 , which facilitated injection and transfer of electrons from t MAPbI 3 perovskite to SnO 2 .…”
Section: Carrier Engineeringmentioning
confidence: 99%
“…In 2021, Lv et al [ 49 ] reported the modification of SnO 2 using dilute CdS QDs. The crystallinity and flatness of SnO 2 were enhanced by the modification of CdS QDs.…”
Section: Quantum Dots As Additives In Perovskite Solar Cellsmentioning
confidence: 99%